REFLECTIONS ON THE EXPERIENCE OF ETHNOGRAPHIC CLASSIFICATION OF THE TURKESTAN POPULATION IN THE RUSSIAN EMPIRE - Ismoiljon Khujakhonov (Modern American Journals, 2025)
This article analyzes the historical-political and methodological approaches to the ethnographic classification of the Turkestan population during the Russian Empire. It examines classification efforts by imperial administrators and researchers in the late 19th and early 20th centuries, based on language, lifestyle, religion, and physical appearance. The article highlights the ambiguity and confusion in the use of terms such as “Sart”, “Kyrgyz”, “Uzbek” and “Tajik”. It emphasizes that the primary goal of ethnographic studies was to facilitate administrative control and organize an effective tax system. The role of language and anthropological traits in ethnic identification, as well as the stance of local intellectuals, is also addressed. The author demonstrates that the classification process was marked by significant uncertainty and inconsistencies.
Keywords: Turkestan, ethnographic classification, Russian Empire, ethnographic studies, ethnic identity.